Pengaruh Motivasi, Pengalaman Kerja dan Disiplin Kerja terhadap Kinerja Karyawan di BSI Kantor Cabang Pembantu Setiabudi 2 - Lenny Yanthiani; Haekal Pirous (Jurnal Dimamu, 2023)
The background of this study is to determine the motivation of work experience and work discipline on employee performance, this is important because every human resource is expected to have good quality. This study aims to determine how the influence of motivation, work experience and work discipline on employee performance at BSI KCP Setiabudi 2, either partially or simultaneously. The object of research is employees at BSI KCP Setiabudi 2, while the type of research is quantitative associative, the type of data is primary data so that a questionnaire is needed to find out employee responses as research objects, and uses observations, interviews, documentation studies and literature studies as a complement. The results showed that there was a significant influence between work motivation on employee performance with the results of the t test where the value of tcount > ttable (7.771 > 2.11991), there was a significant influence between work experience on employee performance with the results of the t test where the value of tcount > ttable (3,623 > 2.11991), there is a significant effect of work discipline with the results of the t test where the value of t count > t table (4.725 > 2.11991), and there is a simultaneous influence of motivation, work experience and work discipline on employee performance with the results of the F test where Fcount > Ftable (10,496 > 3.36 )